2013
DOI: 10.1107/s0907444912048998
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the inhibition ofMycobacterium tuberculosisL,D-transpeptidase by meropenem, a drug effective against extensively drug-resistant strains

Abstract: The crystal structure of M. tuberculosis l,d-transpeptidase (LdtMt2; Rv2518c) has been determined in both ligand-free and meropenem-bound forms. The detailed view of the interactions between meropenem and LdtMt2 will be useful in structure-guided discovery of new antituberculosis drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
106
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(116 citation statements)
references
References 38 publications
9
106
0
1
Order By: Relevance
“…The crystal structure of Ldt Mt2 was recently reported by four independent groups (19)(20)(21)(22). These studies also report molecular interactions with the substrate and the carbapenem class of drugs and the mechanism of catalysis by Ldt Mt2 .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…The crystal structure of Ldt Mt2 was recently reported by four independent groups (19)(20)(21)(22). These studies also report molecular interactions with the substrate and the carbapenem class of drugs and the mechanism of catalysis by Ldt Mt2 .…”
Section: Discussionmentioning
confidence: 73%
“…Although ␤-lactams are rarely used for treatment of M. tuberculosis infection, recent reports demonstrate that the carbapenem subclass of ␤-lactams are effective against a range of M. tuberculosis strains (44)(45)(46). Although certain carbapenems have been demonstrated to bind to and inhibit L,D-transpeptidase activity (19,(21)(22)(23), it is not known if their M. tuberculosis growthinhibitory activity is a result of inhibition of specific or multiple transpeptidases. The in vivo study demonstrated that loss of ldt Mt1 and ldt Mt2 makes M. tuberculosis uniquely susceptible when exposed to a combination of amoxicillin-clavulanate and vancomycin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that ␤-lactams interfere with peptidoglycan biosynthesis and metabolism in multiple ways and eventually results in cell death (17,19). Among ␤-lactams, carbapenems and penems are able to bind and inhibit activities of D,D-transpeptidases, L,D-transpeptidases, and D,D-carboxypeptidases (6,(20)(21)(22)(23)(24)(25)(26). This versatile property of (carba)penems to target multiple enzymes prompted the current study to test the clinical utility of commercially available (carba) penems in M. tuberculosis and M. abscessus isolates from patients.…”
Section: Discussionmentioning
confidence: 99%